Reinforced concrete structures : analysis and design - Fanella, David Anthony (New York : McGraw-Hill, 2011)
'Reinforced Concrete Structures explains the underlying principles of reinforced concrete design and covers the analysis, design, and detailing requirements in the 2008 American Concrete Institute (ACI) Building Code Requirements for Structural Concrete and Commentary and the 2009 International Code Council (ICC) International Building Code (IBC). This authoritative resource discusses reinforced concrete members and provides techniques for sizing the cross section, calculating the required amount of reinforcement, and detailing the reinforcement. Design procedures and flowcharts guide you through code requirements, and worked-out examples demonstrate the proper application of the design provisions.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Buildings, Reinforced concrete; Reinforced concrete construction; Reinforced concrete -- Quality control